Energetic and economic optimization of the yearly performance of three different solar assisted heat pump systems using a mixed integer linear programming algorithm. (15th February 2020) - Simonetti, Riccardo; Moretti, Luca; Molinaroli, Luca; Manzolini, Giampaolo
Highlights: Mixed integer linear programming for optimal management of solar assisted heat pump. Energetic and economic analyses on a yearly basis are carried out. Parametric analysis of the solar modules number and battery size. Dual-source solar assisted heat pump achieves the highest energetic performance. Conventional air-to-water heat pump achieves the lowest operating cost. Abstract: This paper presents a yearly energetic and economic assessment of three different solar assisted heat pump concepts integrated with electrical and thermal storages and applied to a single-family house. The three heat pump-based systems are (i) a conventional air-to-water heat pump plus photovoltaic solar modules, (ii) a water-to-water heat pump coupled to hybrid photovoltaic-thermal solar modules and (iii) a dual source heat pump integrated with hybrid photovoltaic-thermal solar modules. The energetic and economic analysis is performed using physically-based models of each component for different numbers of solar modules and sizes of the electric storage. The maximum economic saving of these highly integrated systems is determined through an optimization algorithm based on the mixed integer linear programming technique. The results show that the dual source heat pump system with the largest battery size is the system that achieves the highest energetic performance, i.e. 77% primary energy saving with respect to traditional boiler-based system, whereas the lowest operating cost and the highest economic saving are obtained using the conventional air-to-water heat pump without any electric storage since it achieves 31% economic saving compared with the baseline system.